2023
DOI: 10.1021/acs.langmuir.3c02019
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Separated Giant Liposomes for Stable Elevation of α-Hemolysin Concentration in Lipid Membranes

Abstract: Staphylococcus aureus α-hemolysin (αHL) is one of the most popular proteins in nanopore experiments within lipid membranes. Higher concentrations of αHL within the lipid membrane are desirable to enhance the mass transport capacity through nanopores. However, the reconstitution of αHL at high concentrations is associated with the problem of membrane lytic disruption. In this study, we present a method that effectively increases αHL concentration while maintaining membrane stability. This method is achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…On the basis of the experimental results mentioned above and related papers, , we discuss the characteristic responses of TS molecules to the DOPC molecular layer. Π for all of the samples utilized, that is, NE, NA, DE, DA, BA, and CA, was maintained at zero for A > 15 Å 2 molecule –1 (Figure S4 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…On the basis of the experimental results mentioned above and related papers, , we discuss the characteristic responses of TS molecules to the DOPC molecular layer. Π for all of the samples utilized, that is, NE, NA, DE, DA, BA, and CA, was maintained at zero for A > 15 Å 2 molecule –1 (Figure S4 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…The phospholipid artificial membrane is used as a model cell membrane to investigate the mechanism of cell response because it is difficult to factor out intrinsic elements and their nature on the mechanism of chemical sensation in living organisms as a result of their complexity. Indeed, interactions between chemical species and functional groups in phospholipid artificial membranes have been reported to be associated with barrier homeostasis of cellular membranes in skin . It has also been reported that membrane fluidity of liposomes is affected by ODs. We recently evaluated the interaction between OD molecules and phospholipid molecular layers based on the spectroscopies and surface pressure ( Π )–area ( A ) isotherms .…”
Section: Introductionmentioning
confidence: 99%